Beyond the Surface: Decoding Pityriasis Versicolor Through Clinical, Dermoscopic and Microbiological Exploration - Priya A. Dsouza; Rochelle C. Monteiro; Meena Dias; Sudhir Haladi Prabhu; Ramesh M. Bhat; Jyothi Jayaraman; Jacintha Martis (Indian Journal of Dermatology)
Background: Pityriasis versicolor (PV) is an asymptomatic, superficial fungal infection caused by the Malassezia species and causes discolouration of the skin leading to altered pigmentation. It is usually a clinical diagnosis, but in doubtful cases wherein potassium hydroxide (KOH) mount is unavailable, alternative modalities like dermoscopy aid in the management. Aims and Objectives: To evaluate the clinical and dermoscopic patterns in PV and correlate with the associated risk factors and study the fungal culture. Materials and Methods: A cross-sectional observational study was conducted for 12 months. A total of 115 patients clinically diagnosed with PV showing positivity on KOH mount were recruited. Dermoscopy was done, following which the scales were scraped and cultured in the laboratory on Saborauds dextrose agar and modified Dixon media, and the results were analysed after 3 weeks. Results: Among the 115 participants, on clinical evaluation, 79 patients had achromic and 36 patients had chromic lesions. The dermoscopic features were categorized into domains such as scaling, pigmentation and other features. Fine scaling was the most common feature observed in 88.7% of the patients. Pigmentary changes were noted in all the patients with non-uniform pigmentation being the most common. We have also observed and described newer dermoscopic findings such as barbed wire fence appearance of ridges and furrows, fluffy cotton ball appearance of hypopigmented perifollicular lesions and sprinkled pepper appearance of pigmented dispersion. Out of the 115 KOH mount positive cases, 51 (44.3%) showed growth on fungal culture with Malassezia furfur being the most common species to be isolated in 18 patients. Conclusions: Dermoscopy is a new, popular non-invasive diagnostic modality, which shows specific features like fine scaling, pigment alteration, ridges and furrows with perifollicular involvement, and can be used to diagnose doubtful cases of PV as an adjunct or substitute to a KOH mount.